The value of intraoperative parathyroid hormone assay in the surgery of mediastinal ectopic parathyroid adenoma (A case series). (August 2019) - Rabiou, Sani; Aminou, Sani M.; Efared, Boubacar; Harmouchi, Hicham; Lakranbi, Marwane; Serraj, Mounia; Ouadnouni, Yassine; Smahi, Mohamed
Abstract: Background and aims: Ectopic parathyroid adenoma is a rare entity. Its clinical management is challenging due to varying locations in the mediastinum. The aim of our study is to report our experience about the preoperative localization of the ectopic parathyroid adenoma and to emphasize the major role of the intraoperative parathyroid hormone assay in such circumstances. Methods: It is a monocentric, retrospective study about patients diagnosed with EPA (ectopic parathyroid adenoma) from January 2015 to December 2016. Clinical aspects, preoperative management as well as the surgical procedures have been analyzed. Results: There were 7 women, with an average age of 59.14 years. Six patients presented with biological disorders of the phosphocalcic metabolism such as spontaneous bone fracture and recurrent renal lithiasis. In one case, EPA was discovered in the setting of malignant hypercalcemia. The topographic preoperative assessment with a cervicothoracic CT (computed tomography) showed spontaneously hyperdense tissular masses of variable localizations in the mediastinum. A Tc-99 m (99mTc - MIBI) scintigraphy was performed in 5 patients and showed uptake in all cases. We performed cervicotomy in 1 case, manubriotomy in 2 patients, neck manubriotomy in 2 cases, total vertical sternotomy in 1 case, and posterolateral thoracotomy in 1 patient. The lesion was localized in the mediastinum in 1 patient in the perithymic fat in 1 case; EPA was laterotracheal in 1 case, retro tracheal in 1 case, intra-thymic in 2 cases, inter-jugulo-carotidian with contact with the left subclavial artery in 1 case, and anterior mediastinal in 1 patient. The 1-h after-parathormonemia following removal of the surgical specimens showed a decrease value of 45 and 80% of the baseline value. No surgical morbidity was noted after an average follow-up of 7.9 months (range of 5–18 months). Conclusion: The preoperative topographic diagnosis of ectopic parathyroid adenoma is challenging for the surgeon despite progress in the morphological assessment. The intraoperative parathyroid hormone assay is a valuable tool for an appropriate surgical management. Highlights: Thoracic surgeons faced difficulties in the management of ectopic parathyroid adenomas in the mediastinal location. The intraoperative assay of parathormonemia helps guide the surgeon in his strategy of complete excision of the ectopic parathyroid adenom Hypocalcemia is a constant postoperative complication and its absence may make questionnable the quality of the tumor resection.